Imagery packed with poetic qualities: A case study on English-Chinese translation of Apple’s advertisements - Cui, Ying; Li, Jie (The Journal of Specialised Translation, 2021)
Advertisements often use poetic devices like images to provide aesthetic pleasure and facilitate promotion. This investigation aims to explore the functions and characteristics of images and outline the linguistic methods to create images in English-Chinese advertisement translation, referring to research on translation, marketing, imagery, and poetics. Image is defined in its broad sense in this study to refer to linguistic expressions that evoke a sensory experience in readers or leave a vivid impression on them. Poetic images can increase the aesthetic value of advertisements, arouse readers' emotional response and influence their attitudes, and facilitate their comprehension and enhance their memorisation. Our corpus is composed of 357 English-Chinese advertisements of Apple Inc., which has been successful in its marketing campaigns in China. The analysis of the corpus shows that 61% of the Chinese translations use images. The major methods to set up images in Chinese translations include explicitation, which is most widely used, accounting for 54% of the total, metaphor, which makes up 37%, balanced structure, which constitutes 32%, and sensory stimulation, which is used in 12% of the examples. Applying those linguistic methods and setting up images in English-Chinese advertisement translation can be an effective way to engage readers and facilitate promotion.